2007
DOI: 10.2350/06-04-0083.1
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-Phenotype Associations in Patients with Severe Hyperinsulinism of Infancy

Abstract: In hyperinsulinism of infancy (HI), unregulated insulin secretion causes hypoglycemia. Pancreatectomy may be required in severe cases, most of which result from a defect in the beta-cell KATP channel, encoded by ABCC8 and KCNJ11. Pancreatic histology may be classified as diffuse or focal disease (the latter associated with single paternal ABCC8 mutations), indicated by the presence of islet cell nuclear enlargement in areas of diffuse abnormality. We investigated genotype-phenotype associations in a heterogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…This mutation is likely to result in a protein which will either be retained in the endoplasmic recticulum or which will reach the cell membrane but will not function properly. The R168C mutation has been previously reported in a patient with CHI [14]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This mutation is likely to result in a protein which will either be retained in the endoplasmic recticulum or which will reach the cell membrane but will not function properly. The R168C mutation has been previously reported in a patient with CHI [14]. …”
Section: Resultsmentioning
confidence: 99%
“…Greer et al [14] have reported a patient who was compound heterozygote for the R168C/R1421C mutations in the ABCC8 gene and had severe, medically unresponsive CHI. No functional characterisation of the R168C mutation has yet been undertaken.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that this patient has recessively inherited HI with the accompanying mutation being undetected (23,30).…”
Section: Inheritance Of Abcc8 and Kcnj11 Mutationsmentioning
confidence: 99%
“…Mutations in nine different genes (ABCC8, KCNJ11, GLUD1, GCK, HADH, SLC16A1, subunits: Kir6.2 encoded by KCNJ11 and SUR1 encoded by ABCC8 gene (2). Both genes are localised in the 11p15.1 region and mutations in these accounts for the majority of CHI patients (3,4,5,6,7,8,9,10,11).…”
Section: Introductionmentioning
confidence: 99%